CONTRIBUTION OF MOTIVATION LEARNING ACHIEVMENT OF CONSTRUCTION MATERIALS STUDENT CLASS OF X TECHNIQUES DRAW BUILDING OF SMK 1 BALIGE - 1982-1997 , Gratia K. Simarmata (CIVED, 2016)
This purpose of the research is determine by existence of result difference learn Construction Drawing Building. Many student get low value in face of Final Exam School (UAS). The research aim to to know how big motivation contribution learn to learn to learning achievement Contruction Material class student of X Tecnique Drawing Building in SMK 1 Balige. This reseach include in correlational type. Responden in this research is student class of X Technique Draw Buillding who following subject Construction Material school year 2015/2016 in SMK N 1 Balige. The selection of the sampel using technique total sampling with amount of sampel 55 student. Data type is used by data primary and data sekunder. Primary data gotten with spreading of kuesioner about learning  motivation which is propagated to student, while data of sekunder is gotten from the UAS class student construction material of X Technique Drawing Buillding. The analytical method that used is descriptive analysis. The test requirement analysis using test of normality and linearity to prove that data swampy forest come from sampel which have normal distribution an linear. Hereinafter examination of hypothesis. Result of this research analysis indicate that value of r 0,534 > 0,05 with Interpretation Coeffcient is too low. The results of this research is shows that contributions equal to 28, 51%. Based of acquire of examination result, can be pulled by contribution to learning achiement class construction material of X Tecnique Drawing of SMK N 1 Balige equal to 28,51%. Keyword: Contribution, Learning Motivation, Learing Achievment.